Uit de Klere(n) 1995. - Késenne, Joannes (Oud-Rekem : Galerie Van Laethem, 1995)
Arink, Karin ; Brouwer, Rolly ; Carlier, Jan ; Creemers, Oscar ; Daenen, Pie ; Favre, Valérie ; Hahn, Wolfgang ; Hirai, Yu ; Meister, Ulrich ; Mistiaen, Carlo ; Nibbering, Annemarie ; Samen, Judith ; Scanga, Bill ; Sochacki, Paul ; Sous, Vera ; Swinnen, Malou ; Takeuchi, Takakazu ; Tersas, Toon ; Togawa, Mitsue ; Van De Gaar, Leonne ; Vertessen, Liliane ; Wurm, Erwin
Uit de Klere(n) 1995, Galerie Van Laethem, Oud-Rekem ; Begijnhofkerk, St. Truiden, 13.08 - 08.10.1995
boek